The double-edged sword of mobilizing citizens via mobile phone in developing countries. (2018) - Erlich, Aaron; Jung, Danielle F.; Long, James D.; McIntosh, Craig
Abstract: New innovations in mobile technology provide an unparalleled opportunity for researchers and organizations to scale communications with citizens in the developing world, but bring new challenges in terms of how to generate and retain engaged users. We report on a number of technical dimensions based on our experience building a bi-directional multi-channel mobile phone platform to engage citizens in South Africa's 2014 presidential election. Specifically, we deployed the "VIP:Voice" platform at national scale to conduct opinion polling, to allow citizens to report on political activity, and to engage citizen monitors for polling stations on election day. Our platform operated across multiple device types, from flip-phones to Twitter, and consequently provides critical lessons on the most effective means of gathering and disseminating a rich variety of data depending on the user's device type. We compare different means of obtaining location in the absence of GPS, and show how different formats for soliciting and entering data generated very differential response rates. Our paper illustrates a number of concrete ways in which platform development driven by smartphone logic does not translate easily for users of more basic mobile phones, including whether questions are presented passively in a menu or pushed to a user's phone, and the format in which user data are entered. This paper is intended to provide actionable guidance for researchers and organizations deploying ICT platforms to interact with citizen users at a national or cross-national scale in international development.